القيم السوسيوثقافية للمجتمع الجزائري في المنهاج التربوي - هياق, إبراهيم (جامعة الوادي - University of Eloued, 2022)
تعتبر القيم في المناهج التعليمية ذات أهمية كبيرة،فهي الجسر الذي تنقل من خلاله المفاهيم الاجتماعية والثقافية إلى الأجيال .يهدف هذا المقال إلى البحث في القيم الاجتماعية والثقافية في محتوى منهاج التربية الإسلامية على مستوى التعليم المتوسط ،من خلال جرد شامل لجميع القيم الاجتماعية والثقافية للمجتمع الجزائري باستخدام أساليب إحصائية محددة ( التكرارت،النسب المئوية) وتحليل نتائجها. Abstract: Values in educational programs are of great importance as they form the bridge through which social and cultural concepts are passed down to generations. This article aims to research socio-cultural values in the content of the curriculum of Islamic education at the level of intermediate education, through an exhaustive inventory of all the social and cultural values of Algerian society using a set statistical method (frequencies, percentages) and analyzing their results.
دراسة تحليلية لمنهاج التربية الإسلامية لمرحلة التعليم المتوسط
مقال
Keywords: القيم السوسيوثقافية ؛ المنهاج ؛ المجتمع الجزائري ؛ التعليم المتوسط ؛ التربية الإسلامية; sociocultural values; curriculum; Algerian society; intermediate education; Islamic education